Efficiency of Indonesia Sharia Bank (BSI): A Data Envelopment Analysis Approach - Syatir, Ahmad; Yunus, Rita; Tuty, Farida Millias; Sari, Novita (Al-Infaq: Jurnal Ekonomi Islam, 2025)
This research aims to analyze the level of efficiency of Bank Syariah Indonesia (BSI) as a merged bank. The data used comes from secondary data from BSI's financial reports for the 2022-2023 period. Data was analyzed using the Data Envelopment Analysis (DEA) method from an asset approach, which is input-oriented. The data analyzed consists of three input variables (Labor Costs, Promotion Costs, and Other Costs), and three output variables (Profit Sharing Financing, Rental Financing, and Securities Owned). The processed data shows that BSI's efficiency level is relatively high with an average efficiency value of 0,78 on a maximum scale of 1. However, this value is still categorized as inefficient.  Structurally, two input variables were found that played a role in this inefficiency, namely Labor Costs and Other Costs, each of which was detected in the second to fourth quarters of 2022. Based on the DEA results, improvements in the level of efficiency, according to the projected values, can be given treatment by decreasing Labor Costs and Other Costs